Meningkatkan Hasil Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Jigsaw pada Siswa SMP - Nasruddin Nasruddin; Zainal Abidin (Universitas Negeri Makassar, 2017)
In this study, we discuss about Jigsaw type cooperative learning model to improve mathematics learning outcomes on the basic competence of cubes and beams of students of class VIIIA SMP. This research is a Classroom Action Research (CAR) conducted in SMPN 2 Lasusua Year Learning 2016/2017 even semester. This study uses two cycles, each cycle has procedures such as planning, action, observation and reflection. The results of this study indicate the implementation of cooperative learning model jigsaw type can improve student learning outcomes in mathematics subjects. The value after the first cycle action increased compared with the initial test of 45,85 to 65,75. Furthermore the average score of students after the second cycle action increased compared with the average score of students on the implementation of the first cycle action that is 65,75 to 80,60 and has met the predetermined performance indicators that 85% of students have received a minimum score of 65.